2011
DOI: 10.1111/j.1708-8208.2011.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Implant Survival Rates after Osteotome‐Mediated Maxillary Sinus Augmentation: A Systematic Review

Abstract: The transalveolar sinus augmentation technique could be a viable treatment in case of localized atrophy in the posterior maxilla even in case of minimal residual bone height. The prognosis can be more favorable when the residual ridge is at least 5 mm high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
172
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(182 citation statements)
references
References 37 publications
6
172
1
3
Order By: Relevance
“…Results from the work of Kfir et al and Mazor et al are well within the range of 92.7-96.9 % survival reported by a systematic review for sinus lift using the transalveolar approach [5,6,20,22].…”
Section: Discussionsupporting
confidence: 70%
“…Results from the work of Kfir et al and Mazor et al are well within the range of 92.7-96.9 % survival reported by a systematic review for sinus lift using the transalveolar approach [5,6,20,22].…”
Section: Discussionsupporting
confidence: 70%
“…(3,4) Recently, a systematic review of the literature showed that crestal sinus lift can be an effective treatment option, reporting a mean weighted survival rate of 95% after 5 years of function. 26 The same review also showed that the majority of failures occurred during the first year after treatment. However, limitations of this procedure include: limited accessibility and visibility for elevation of the sinus membrane and inability to diagnose and treat membrane perforations.…”
Section: Discussionmentioning
confidence: 92%
“…Genellikle rezidüel kemik miktarı >5 mm'den daha fazla ise transkrestal yaklaşım uygulanırken, kemik miktarının <5mm'den daha az olması durumunda lateral pencere yaklaşımı tercih edilmektedir. 47,48 Lateral yaklaşım; maksiller sinüsün elevasyonunu içeren konvansiyonel teknik olup, maksillanın lateral tarafından, zigomatik yüzünden sinüs membranının elevasyonu ve graft materyalinin yerleştirilmesi işlemidir. 45 Bu işlem ardışık şekilde, ilk olarak flapin kaldırılması, sırasıyla sinüs lateral duvarına pencere açılması, sinüs membranının elevasyonu ve boşluk oluşturulması, ardından periosteum ile çevrili greft materyalinin yerleştirilmesi ve son olarak flapin kapatılmasından oluşmaktadır.…”
Section: Görüntü Kalitesiunclassified
“…Bu teknikle kemik yüksekliğinde 3mm'den 9 mm'ye kadar artış sağlanmaktadır. 47,48 Günümüzde komplikasyonları ve hasta rahatsızlığını azaltmak amacıyla konvansiyonel yöntemlerin dışında farklı cerrahi teknikler geliştirilmiştir. Bunlardan biri de piezoelektrik tekniğidir.…”
Section: Görüntü Kalitesiunclassified